The Effects of Multimodal Exercise Program on Functional Capacity and Quality of Life in Elderly Patients with Parkinson\'s Disease - Abbas Abdel Amir Nasser; khosro Jalali Dehkordi; Mahmoud Nasser Radhi; Farzaneh Taghian; Ahmad Chitsaz (Elderly Health Journal)
Introduction: Parkinson's disease (PD) is a degenerative neurological illness characterized by various motor and non-motor symptoms that can lead to varying degrees of functional impairment. This study aims to investigate the effects of a multimodal exercise program (MEP) on functional capacity and quality of life in elderly patients with PD.